HUBUNGAN KREATIVITAS MENGAJAR GURU DENGAN PRESTASI BELAJAR SISWA - Monawati Monawati.; Fauzi Fauzi. (Universitas Syiah Kuala, 2018)
Teaching creativity is related to teaching abilities that can create a conducive atmosphere that makes students feel comfortable and challenged in learning, by making new combinations and connecting new ideas based on information data or elements that already exist. Teaching and learning activities in schools are oriented towards high academic learning achievement by all students, teachers who have high teaching creativity will be able to provide learning achievements to their students. Student learning achievement is the results achieved by students from their learning activities taken to obtain knowledge and skills that can be realized by changes in attitudes and behavior. Student learning achievement is strongly influenced by the creativity of a teacher as in choosing teaching methods, teaching media, quality and careful in seeing the potential of children in the school environment. A teacher's creativity greatly influences a student's learning achievement. In this case the teacher who has the potential to creativity in class is very positive influence on the progress of student learning achievement. To produce high student achievement it is necessary for teachers to hone their creative abilities to the maximum extent possible.